Effect of cobalt particle morphology on the properties of polycrystalline diamond composite - Chenjie SONG; Wenliang WEI; Jinjie WANG; Zhihai LI; Zhihua SI; Fengqin LIU; Kai HUANG (Jin'gangshi yu moliao moju gongcheng, 2023)
Spherical and whisker-like cobalt particles were doped into the diamond powders to synthesize the PDC compacts under the HPHT conditions, to investigate the effect of their morphology on the properties of PDC. It was found that the two morphologies of cobalt powder have significant differences in physical characteristics, such as microstructure, porosity, magnetic properties, and crystallinity. When they were used to synthesize PDC samples, it was found that there were noticeable differences in interface bonding morphology, abnormal growth of interface WC, impact strength, and wear resistance. PDC synthesized with spherical cobalt powder had better comprehensive performance than PDC synthesized with whisker-like cobalt powder.